Land Use/Land Cover Change Detection using Remote Sensing and GIS Technology in Surat Municipal Corporation Area, Gujarat, India - Kamboj, R. D.; Das, Lopamudra; Patel, Nitin; Gohil, Mitesh (Indian Forester, 2021)
The present study encompasses the Land use/land cover (LU/LC) change detection in Surat Municipal Corporation (SMC) area by using Geographical Information Systems (GIS) and Remote Sensing (RS) technology, over a period of a decade at an interval of 5 years, i.e., for the year 2005, 2011 and 2016. The comparison of LU/LC in 2005, 2011 and 2016 derived from Surat Municipal Corporation map and satellite imagery reveals that, there is a steady growth in dense tree cover, open tree cover, built-up area and aquaculture area. On the other hand, open land area declined correspondingly. Moreover the overall tree cover of Surat Municipal Corporation area has increased from 1041.68 ha to 1139.98 ha from the year 2005 to 2016 which may be due to presence of Tapi riverine area within the study area as well as plantation derives undertaken as a part of Green Surat Campaign done by Surat Municipal Corporation Authority, State Forest Department and other organizations.